When the Home Is Also the Workplace: Women migrant domestic workers’ experiences with the ‘live-in’ policy in Singapore and Hong Kong - Joo Tan, Shih (Anti-Trafficking Review, 2023)
This article examines the link between the mandatory live-in policy and the unsafe working and living conditions of women migrant domestic workers. This policy has been rationalised on the principles of the inviolability of the private home and challenges around regulating and enforcing labour protections in the home-workplace but has, in practice, increased migrant domestic workers’ precarity and exploitation. Drawing on empirical research in Singapore and Hong Kong, the article demonstrates how the live-in policy operates in tandem with inadequate labour and migration regulations to produce a situation where poor working and living conditions are an enduring part of workers’ employment and everyday lives. It contributes to research that has highlighted the gendered dynamics and exclusionary bordering practices that shape waged domestic labour, and considers the implications this may have for the well-being and security of women migrant domestic workers.